A comparative review of microplastics in lake systems from different countries and regions. (January 2022) - Yang, Siyuan; Zhou, Ming; Chen, Xin; Hu, Liping; Xu, Yifeng; Fu, Weng; Li, Chao
Abstract: Microplastics, as defined here as plastics with a diameter of <5 mm, can impose severely detrimental impacts on the environment and can now be commonly found in different water bodies. To date, the status of microplastics in limnic systems, which have different hydrologic systems compared to other water bodies such as oceans or rivers, has rarely been reviewed. In the present study, the microplastic pollutants in different countries and regions were comparatively investigated in terms of their abundances, morphologies, and polymer types in the water and sediments of lakes. The concentration and characteristics of microplastics were found to be largely different across countries and regions, which was related to the local development level and economic structure. The migration paths of microplastics in the inner and external limnic ecosystems further revealed the causes for the regional divergence in microplastics. Policy developments in different countries and regions were also discussed to highlight the urgency of better controlling microplastic pollution in lake systems. The characteristics of microplastics vary across countries and regions, depending on the local development level and economic structure. Highlights: The abundances and properties of microplastics in the lakes from different areas largely varied. Microplastic pollution was closely related to the local development level and economic structure. The migration paths of microplastics in the inner and external limnic ecosystems were revealed. The policy developments for controlling microplastic pollution were also discussed.